Features of personal names of Russian Germans of the Tomsk region; Лингвистические и культурологические аспекты современного инженерного образования - Щеголихина Ю. В. Юлия Викторовна (2023, 2023)
This article studies the anthroponyms of Russian Germans in close correlation with specific families of this ethnic community in biographical discourse. The book «Remember Your Name» served as a factual base. This study also examines anthroponyms of Russian Germans in folk discourse. In the latter case, the study was carried out based on the results of an expedition to the Kozhevnikovsky area of the Tomsk region